The predictive value of serum procalcitonin for non-invasive positive pressure ventilation in the patients with acute exacerbation of chronic obstructive pulmonary disease - Liu, Linlin (Medicine (Baltimore), 2021)
This study aimed to estimate the value of serum procalcitonin (PCT) for non-invasive positive pressure ventilation (NIPPV) prediction in the patients with acute exacerbation of chronic obstructive pulmonary disease (AECOPD). A total of 220 AECOPD patients were divided into NIPPV group (n = 121) and control group (routine treatment, n = 99) based on the routine standards and physicians’ experience. Logistic regression analysis was performed to identify the independent factors for NIPPV treatment. Additionally, the predictive values of the factors were measured through receiver operation characteristic (ROC) curve. NIPPV group and control group showed significant differences in respiratory rate (RR), PaO(2), PaCO(2), pH, oxygenation index, erythrocyte sedimentation rate (ESR), neutrophil, CRP (C-reaction protein), and PCT (P < .05 for all). PCT, CRP, PaCO(2), RR, and neutrophil were independently correlated with NIPPV treatment in AECOPD. ROC curve showed that PCT had superior predictive value, with AUC of 0.899, the sensitivity of 86%, and the specificity of 91.9%. The cut-off value of serum PCT for NIPPV prediction was 88.50 ng/l. AECOPD patients who require NIPPV treatment frequently have high levels of PCT, CRP, PaCO(2), RR and neutrophil. Serum PCT may be employed as an indicator for NIPPV treatment in AECOPD patients.